Vitellogenin gene expression in males of the Antarctic fish Trematomus bernacchii from Terra Nova Bay (Ross Sea). A role of environmental cadmium? - CANAPA, Adriana; BARUCCA, MARCO; GORBI, STEFANIA; BENEDETTI, MAURA; BISCOTTI, MARIA ASSUNTA; OLMO, ETTORE; REGOLI, Francesco; ZUCCHI S; NIGRO M (Chemosphere, 2007)
Synthesis of vitellogenin (VTG) in male fish is a widely recognized effect for estrogenic pollutants in temperate environments, while similar investigations are still lacking for Antarctic organisms. In this study, a preliminary characterization of vitellogenin gene expression was performed by RT-PCR in the key species Trematomus bernacchii sampled in different phases of reproductive cycle and food availability. Females exhibited the highest gene expression during the spawning period, but VTG mRNA was always detected also in males; a significant increase of gene expression was observed both in males and females at the end of the feeding season. These results were not fully supported by a differential exposure to phyto- or anthropogenic estrogens during the planctonic cycle; on the other side, the endocrine properties of cadmium, naturally elevated in Terra Nova Bay and increasing during algal bloom, would explain both the presence of VTG mRNA in males and the seasonal changes of gene induction. Laboratory exposures did not reveal short-term estrogenic effects of cadmium while an elevated responsiveness of T. bernacchii was observed toward a classical estrogenic receptor agonist (17β-estradiol). Different hypotheses were considered to suggest delayed endocrine effects of cadmium, including the early interaction with other cellular detoxification systems or alterations at multiple levels of the hypothalamus-pituitary-gonad-liver axis. Although molecular mechanisms of VTG gene expression in males of T. bernacchii remain unclear, obtained results provide interesting insights on this species which should stimulate future research activities.